Lesbian, Gay, and Bisexual Students Experiencing Homelessness and Substance Use in the School Context: A Statewide Study. (15th August 2022) - Moore, Hadass; De Pedro, Kris
ABSTRACT: PURPOSE: This study explored differences between lesbian, gay, and bisexual (LGB)‐housed and homeless students regarding substance use patterns on and off school grounds and the unique contribution of homelessness to substance use in school. METHODS: Data were from the 2013‐2015 California Healthy Kids Survey, a statewide survey of school protective factors and risk behaviors. A representative sample of 9th‐ and 11th‐grade students (N = 20, 337) was used. Comparisons between housed (n = 19, 456) and homeless (doubled up: n = 715; acute homeless: n = 166) LGB students were conducted. We used chi‐square tests to compare rates of lifetime, past‐30‐day, and in‐school substance use and conducted multivariate logistic regression models for each substance use variables. RESULTS: Chi‐square test results indicated significant differences in rates of substance use among students experiencing homelessness (both categories) and housed LGB students. Lesbian, gay, and bisexual students experiencing homelessness were more likely to report substance use off and on school grounds. Results from logistic regression analyses indicated that LGB students who experience homelessness were significantly more likely to report recent and in‐school substance use. For example, students experiencing acute homelessness were about 3 times as likely to report heavy episodic drinking (adjusted odds ratio [AOR] = 3.13; 95% confidence interval [CI] = 2.13, 4.26) and more than 5 times as likely to smoke marijuana in school (AOR = 5.38; 95% CI = 3.46, 8.36), compared to housed LGB students. CONCLUSIONS: LGB students who experience homelessness are at higher risk than housed LGB students of substance use on and off school grounds. Findings highlight the need to provide support in the school context for this subpopulation.